Inhibition of tiRNA-Gly-GCC ameliorates neointimal formation via CBX3-mediated VSMCs phenotypic switching - Rong, Zhihua; Li, Fengshi; Zhang, Rui; Niu, Shuai; Di, Xiao; Ni, Leng; Liu, Changwei (Frontiers in cardiovascular medicine, 2023)
tRNA-derived fragments (tRFs) are a new class of non-coding RNAs involved in a variety of pathological processes, but their biological functions and mechanisms in human aortic smooth muscle cells (HASMCs) phenotype transition and vascular intimal hyperplasia are unclear. tiRNA-Gly-GCC is upregulated in synthetic HASMCs, atherosclerotic arteries, plasma, and the balloon injured carotid artery of rats. Functionally, the inhibition of tiRNA-Gly-GCC represses HASMCs proliferation, migration, and reversed dedifferentiation, whereas the overexpression of tiRNA- Gly-GCC have contrary effects. Mechanistically, tiRNA-Gly-GCC performs these functions on HASMCs downregulating chromobox protein homolog 3 (CBX3). Finally, the inhibition of tiRNA-Gly-GCC could ameliorate neointimal formation after vascular injury . tiRNA-Gly-GCC is a mediator of HASMCs phenotypic switching by targeting CBX3 and inhibition of tiRNA-Gly-GCC suppresses neointimal formation.